Modeling Decisions for Artificial Intelligence : 17th International Conference, MDAI 2020, Sant Cugat, Spain, September 2-4, 2020 : proceedings /: 17th International Conference, MDAI 2020, Sant Cugat, Spain, September 2-4, 2020 : proceedings. ([2020]) - Unknown
No abstract available